2010
DOI: 10.1016/j.otsr.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder hemi arthroplasty radiological and clinical outcomes at more than two years follow-up

Abstract: Level IV. Therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
0
23
0
4
Order By: Relevance
“…A smaller, gradual deterioration in joint evaluation scores has been reported after hip and knee replacement (Ritter et al 2004). Due to differences in weight load on joints of the upper and lower extremities, these results may not be directly extrapolated to our cohort, and outcome of shoulder replacement is considered to be almost stable after one year (Wirth et al 2006, Ohl et al 2010, Cazeneuve and Cristofari 2011). Thus, we presume that deterioration or improvement in WOOS scores as a result of the time delay was of minor importance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller, gradual deterioration in joint evaluation scores has been reported after hip and knee replacement (Ritter et al 2004). Due to differences in weight load on joints of the upper and lower extremities, these results may not be directly extrapolated to our cohort, and outcome of shoulder replacement is considered to be almost stable after one year (Wirth et al 2006, Ohl et al 2010, Cazeneuve and Cristofari 2011). Thus, we presume that deterioration or improvement in WOOS scores as a result of the time delay was of minor importance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A possible disadvantage of cemented hemiarthroplasty is severe glenoid erosion. [23][24][25][26] The purpose of the current retrospective study was to evaluate the long-term results of shoulder hemiarthroplasty in patients with RA and to provide recommendations for clinical practice and future research.…”
mentioning
confidence: 99%
“…Nevertheless, radiological glenoid deterioration is not correlated with pain or deterioration of clinical results. 34 Periprosthetic fractures were not seen in this series, possibly because of the absence of stress shielding with resurfacing implants. [50][51][52] Stemmed prostheses create a stress riser effect at the tip of the stem in the midshaft of the humerus.…”
Section: Discussionmentioning
confidence: 65%
“…19,32,33 The current authors' early results are slightly better compared with other results reported with stemmed implants. [34][35][36][37][38] The authors tried to minimize selection bias in this study by only including patients with an intact cuff (less than 1-cm rotator cuff tear) and glenohumeral osteoarthritis. Measurement bias was minimized by having assessors who were not involved with the original surgery.…”
Section: Discussionmentioning
confidence: 99%